Phosphate Uptake from Phytate Due to Hyphae-Mediated Phytase Activity by Arbuscular Mycorrhizal Maize - Wang, Xin-Xin; Hoffland, Ellis; Feng, Gu; Kuyper, Thomas W. (Frontiers in Plant Science, 2017)
Phytate is the most abundant form of soil organic phosphorus (P). Increased P nutrition of arbuscular mycorrhizal plants derived from phytate has been repeatedly reported. Earlier studies assessed acid phosphatase rather than phytase as an indication of mycorrhizal fungi-mediated phytate use. We investigated the effect of mycorrhizal hyphae-mediated phytase activity on P uptake by maize. Two maize (Zea mays L.) cultivars, non-inoculated or inoculated with the AM fungi Funneliformis mosseae or Claroideoglomus etunicatum, were grown for 45 days in two-compartment rhizoboxes, containing a root compartment and a hyphal compartment. The soil in the hyphal compartment was supplemented with 20, 100 and 200 mg P kg-1 soil as calcium phytate. We measured activity of phytase and acid phosphatase in the hyphal compartment, hyphal length density, P uptake and plant biomass. Our results showed: (1) phytate addition increased phytase and acid phosphatase activity, and resulted in larger P uptake and plant biomass; (2) increases in P uptake and biomass were correlated with phytase activity but not with acid phosphatase activity; (3) lower phytate addition rate increased, but higher addition rate decreased hyphal length density. We conclude that P from phytate can be taken up by arbuscular mycorrhizal plants and that phytase plays a more important role in mineralizing phytate than acid phosphatase.